Comorbidities of scars in China: a national study based on hospitalized cases. Issue 1 (10th June 2021) - Kong, Weishi; Xiao, Yongqiang; Wang, Baoli; Zhu, Zhe; Hu, Lunyang; Tang, Hongtai; Wang, Kangan; Fang, He; Shi, Ying; Long, Jianyan; Gan, Lanxia; Wang, Haibo; et al.
Abstract: Background: Scar comorbidities seriously affect the physical and mental health of patients, but few studies have reported the exact epidemiological characteristics of scar comorbidities in China. This study aimed to investigate the prevalence of scar comorbidities in China. Methods: The data of 177, 586 scar cases between 2013 and 2018 were obtained from the Hospital Quality Monitoring System based on the 10th edition of the International Classification of Diseases coding system. The total distribution of scar comorbidities and their relationship with age, aetiology and body regions were analysed. Results: Six comorbidities (contracture, malformation, ocular complications, adhesion, infection and others) were the main focus. In general, male patients outnumbered females and urban areas outnumbered rural areas. The proportion of contractures was the highest at 59, 028 (33.24%). Students, workers and farmers made up the majority of the occupation. Han Chinese accounted for the majority of the ethnic. The highest proportion of scar contracture occurred at 1–1.9 years of age (58.97%), after which a significant downward trend was observed. However, starting from 50 years of age, ocular complications increased gradually and significantly, eventually reaching a peak of 34.49% in those aged >80 years. Scar contracture was the most common comorbidity according to aetiology, and the highest proportion was observed in patients who were scalded (29.33%). Contractures were also the most frequent comorbidity in hands (10.30%), lower limbs (6.97%), feet (6.80%) and upper limbs (6.02%). The mean and median hospitalization durations were 12.85 and 8 days, respectively. Conclusions: Contractures were the most common comorbidities, and different comorbidities tended to occur at different ages and with different causative factors.